2021
DOI: 10.1002/ejlt.202000297
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Phospholipids to Make Pharmaceutical Form Line Extensions

Abstract: This review describes the use of phospholipid excipients to make Pharmaceutical Form (Dosage Form) Line Extensions of existing drugs as part of a Product Life Cycle Management. Product examples and development candidates, which show the versatility of phospholipids as key excipients in formulations to develop line extension drug products for any administration route by reformulating existing products, are provided. The resulting patented products enable the application of a drug substance for another administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 213 publications
(162 reference statements)
0
6
0
Order By: Relevance
“…Moreover, due to the structure, we get targeted therapy as it penetrates the imperfect vessels produced by tumors, and the addition of polyethylene glycols on the surface may increase the time that cisplatin stays in the human bloodstream. Preclinical studies of lipoplatin revealed less nephrotoxicity than cisplatin [ 82 , 83 ].…”
Section: Nanocarriers Of Platinum and Palladium Complexesmentioning
confidence: 99%
“…Moreover, due to the structure, we get targeted therapy as it penetrates the imperfect vessels produced by tumors, and the addition of polyethylene glycols on the surface may increase the time that cisplatin stays in the human bloodstream. Preclinical studies of lipoplatin revealed less nephrotoxicity than cisplatin [ 82 , 83 ].…”
Section: Nanocarriers Of Platinum and Palladium Complexesmentioning
confidence: 99%
“…Based on the findings from our screen and subsequent analyses indicating ratiometric drug synergy between MRX-2843 and vincristine, we developed multiagent lipid nanoparticles closely related in lipid composition to FDA-approved products such as AmBisome and Vyxeos, both of which are comprised of phosphatidylcholine, phosphatidylglycerol, and cholesterol [55]. To further enhance the feasibility of clinical-scale manufacturing, we also devised a method to co-load defined ratios of MRX-2843 and vincristine using a gradient-based method which is notable in its typically high encapsulation efficiency, scalability, and reproducibility, as well as its utilization to manufacture FDA-approved products, Onivyde and Doxil [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…Brixadi® is currently being used in the NIDA-funded Clinical Trials Network's multi-center randomized controlled trial Medication treatment for Opioid use disorder in expectant Mother (MOMs), comparing sublingual and long-acting buprenorphine during pregnancy and one year postpartum 68 . Brixadi® product does not use NMP as part of the delivery device 69 . Long-acting buprenorphine has limited but increasing data in pregnancy suggesting its safety and efficacy in the postpartum population, therefore, the postpartum period may be an ideal time to transition 11,70,71 .…”
Section: Alternative Routes Of Administrationmentioning
confidence: 99%